Analysis of Average Land Surface Temperature of Java Island, Indonesia in 2024 using reduceRegions in Google Earth Engine - Nasution, Rafly Aulya Rizky; Rakuasa, Heinrich; Turi, Fadlan; Hidayatullah, Muh; Latue, Philia Christi (Journal of Selvicoltura Asean, 2024)
This study presents a comprehensive analysis of the average Land Surface Temperature (LST) of Java Island, Indonesia, for the year 2024, utilizing the reduceRegions function in Google Earth Engine (GEE). Rapid urbanization and environmental changes on Java Island have significant implications for its climate and thermal conditions, necessitating effective monitoring and analysis of LST. The research employs satellite-based remote sensing techniques to assess the relationship between vegetation cover and surface temperatures, revealing that areas with higher vegetation density tend to exhibit lower surface temperatures. This finding aligns with previous studies, underscoring the importance of green spaces in urban environments. The analysis not only contributes to a deeper understanding of Java Island’s environmental dynamics but also provides critical insights for policymakers and urban planners. The results can inform strategies for climate adaptation and sustainable development, addressing ongoing environmental challenges. Limitations of the study are acknowledged, and recommendations for future research are proposed, emphasizing the need for continued exploration of LST variations in relation to urbanization and climate change. Overall, this research serves as a valuable resource for enhancing environmental management practices on Java Island and similar regions facing rapid development.